Attitude and practice of brachytherapy in India: a study based on the survey amongst attendees of Annual Meeting of Indian Brachytherapy Society - Gandhi, Ajeet Kumar; Sharma, Daya Nand; Julka, Pramod Kumar; Rath, Goura Kishor (Journal of Contemporary Brachytherapy, 2015)
Purpose: We performed a survey amongst attendees of the 4th Annual Meeting of Indian Brachytherapy Society to study the patterns of brachytherapy practice and attitude towards brachytherapy use. Material and methods : A 19-point questionnaire was designed and e-mailed to the attendees immediately after the conference. Descriptive analysis of the responses were done and satisfaction index was used as a tool for evaluation of the program effectiveness. Binomial test was used to assess the difference between distributions of responses and Mann-Whitney U test was used to assess the correlation between responses. P value (2-tailed) of < 0.05 was taken significant for all statistical analysis. Results : Of a total of 202 attendees, 90 responded to the survey (response rate: 44.5%). Seventy-two percent belonged to an academic institute while 28% belonged to non-academic institutes. Eighty-six percent were radiation oncologists and 10% were medical physicists. Eighty-nine percent respondents used high-dose-rate, 14% – pulse-dose-rate, and 13% used low-dose-rate brachytherapy facility. Orthogonal X-rays, computed tomography, and magnetic resonance imaging was used for brachytherapy planning by 56%, 69%, and 14%, respectively. Ninety-three percent of them thought that lack of training is a hurdle in practicing brachytherapy and 92% opined that brachytherapy dedicated meetings can change their perception about brachytherapy. Seventy percent respondents admitted to make some changes in their practice patterns after attending this meeting. Ninety-seven percent of them would like to attend future meetings and 98% felt the need to include live workshops, hands on demonstrations, and video presentations in the scientific programme. Conclusions : The survey highlights a positive attitude towards increasing brachytherapy use, and may serve as an important guiding tool in designing teaching and training programmes; thus overcoming the hurdles in successful and widespread use of a quality brachytherapy programme at radiotherapy centers.